Development of Hand Doll Media on Science Learning Students of Class V Elementary School 6 Srikaton - Aldian, Giri; Frima, Aren; Egok, Asep Sukenda (Widyagogik, 2022)
This study aims to determine the Hand Puppet Media in Science Learning Class V SD Negeri 6 Srikaton and find out how to develop a Hand Puppet Media in Science Learning Class V SD Negeri 6 Srikaton which is valid and practical. This study uses a 4-D development model. The instruments used to measure the quality of the developed hand puppet media include validation sheets and practicality questionnaires. The product of this research is in the form of hand puppets on theme 1 sub theme 1 learning 1 in class V SD Negeri 6 Srikaton. So that this study shows the results of the entire validation component of the expert team including the valid category with an average score of 0,84 for all validators. The practicality of hand puppets received a practical response with an average score of all practicality tests, which was 91,10 %, this indicates that the hand puppet media is already practical.